Digital Literacy of Islamic Religion Educators as a Companion to the Halal Product Process Through the Sihalal Application for Snack Food Businesses in Serdang Bedagai District - Sari, Ratna; Lubis, Suwardi; Pohan, Syafruddin (Journal of Social Interactions and Humanities, 2024)
This research aims to analyze the digital literacy skills of Islamic Religious Counselors who have additional duties as Halal Product Process Assistants in halal applications. The qualitative method with a descriptive approach is the method used in this research. The results of this research show that Islamic Religious Counselors still need to be equipped with adequate digital literacy skills in order to face technological developments. The phenomenon occurs when Islamic Religious Counselors who serve as Halal Product Process Assistants carry out activities in the field turns out that there are still many snack business actors who do not know the registration procedures and other matters related to the obligation to register the snack food business products of these business actors